2017
DOI: 10.1128/aac.00245-17
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxypyrimidine-2,4-Diones as Novel Hepatitis B Virus Antivirals Targeting the Viral Ribonuclease H

Abstract: Hepatitis B virus (HBV) RNase H (RNH) is an appealing therapeutic target due to its essential role in viral replication. RNH inhibitors (RNHIs) could help to more effectively control HBV infections. Here, we report 3-hydroxypyrimidine-2,4-diones as novel HBV RNHIs with antiviral activity. We synthesized and tested 52 analogs and found 4 that inhibit HBV RNH activity in infected cells. Importantly, 2 of these compounds inhibited HBV replication in the low micromolar range. KEYWORDS RNase H, antiviral agents, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The HPD chemotype was initially designed by us to dually inhibit the RT pol and INST of HIV-1 (Figure ), which also inhibited similar enzymes of other viruses. , The design was based on a well-known NNRTI 17 which has an N–H at the 3 position flanked by two carbonyl groups. The N–H group forms a key H-bond with K101 of RT and thus is typically considered intolerable toward SAR.…”
Section: Pharmachophore-based Design Of Hiv-1 Rt Rnase H Inhibitor Typesmentioning
confidence: 99%
“…The HPD chemotype was initially designed by us to dually inhibit the RT pol and INST of HIV-1 (Figure ), which also inhibited similar enzymes of other viruses. , The design was based on a well-known NNRTI 17 which has an N–H at the 3 position flanked by two carbonyl groups. The N–H group forms a key H-bond with K101 of RT and thus is typically considered intolerable toward SAR.…”
Section: Pharmachophore-based Design Of Hiv-1 Rt Rnase H Inhibitor Typesmentioning
confidence: 99%
“…Interestingly, among the N-hydroxyimide derivatives tested in HBV replication assays, the best Nhydroxyisoquinolinedione derivative, compound 86 ( Figure 16), had an EC 50 of 1.4 µM and a CC 50 of 99 µM, while Edwards et al (2019) have recently identified a more potent N-hydroxypyridinedione derivative, compound A23, with an EC 50 of 0.11 µM and a CC 50 of 33 µM resulting in a good selective index. In addition, in a screening of related compounds using a cell-based HBV replication assay Huber et al (2017) have identified two 3'-hydroxypyrimidine-2,4-diones with less potent inhibitory activity (EC 50 s in the range of 5.5-8.0 µM) but low toxicity (CC 50 >100 µM). While no direct experimental evidence of RNase H inhibition by these compounds was provided, other biochemical studies have shown HBV RNase H inhibition by N-hydroxypyridinediones also blocking the synthesis of plus-strand DNA and causes the accumulation of RNA/DNA heteroduplexes in viral capsids (Edwards et al, 2017).…”
Section: Active Site Human Hbv Rnase H Inhibitorsmentioning
confidence: 99%
“…Expression of functional recombinant HBV RNaseH [7] prompted development of pipelines of biochemical and cellbased screening assays that are sensitive to RNaseH inhibition. Over 130 RNaseH inhibitors have been identified that suppress HBV replication in culture with 50% effective concentrations (EC 50 ) from low micromolar values to ~100 nM, primarily in three chemotypes, the α-hydroxytropolones (αHT), N-hydroxyisoqinonlinediones (HID), and Nhydroxypyridinediones (HPD) [8][9][10][11][12] (Fig. 1).…”
Section: The Rnaseh As a Drug Targetmentioning
confidence: 99%